Managing Consumer Returns in a Competitive Environment - Shulman, Jeffrey D.; Coughlan, Anne T.; Savaskan, R. Canan (Management Science, 2011)
This paper investigates the pricing and restocking fee decisions of two competing firms selling horizontally differentiated products. We model a duopoly facing consumers who have heterogeneous tastes for the products and who must experience a product before knowing how well it matches with their preferences. The analysis yields several key insights. Restocking fees not only can be sustained in a competitive environment, but also are more severe when consumers are less informed about product fit and when consumers place a greater importance on how well products' attributes fit with their preferences. We compare the competitive equilibrium prices to a scenario in which consumers are certain about their preferences and find conditions defining when consumer uncertainty results in higher equilibrium prices. Comparison to a monopoly setting yields a surprising result: Equilibrium restocking fees in a competitive environment can be higher than those charged by a monopolist. This paper was accepted by Jagmohan S. Raju, marketing.